PREDIKSI HARGA EMAS MENGGUNAKAN METODE SINGLE MOVING AVERAGE: Array - Suwandi, Andri (Universitas Harapan Medan, 2020)
Gold sales should indeed be done by using a method that is easy to understand, namely to facilitate buyers and traders in conducting mortgage and predict the rise and fall of gold prices. To determine the gold price prediction using the Single Moving Avatar method, this method has a very wide application, although simple, because this method is only developing methods of the average. Some people have. Hopefully this system can help the community. Here the author provides solutions to facilitate pawnshop employees in conducting gold auctions. Single moving avarage is a method used to build a knowledge-based system. The source of knowledge of the system is obtained by collecting gold sales data. Therefore there are many problems in determining the price range and predicting the price of gold. The first step in solving a problem is by first identifying the scope of the problem to be solved, this also applies to any Artificial Intelligence (AI) programming.